INFLUENCE OF ISLAM ON MENTAL HEALTH - Andriyani; Fatimah; Rahmah, Nisa Aulia; Alifia Putri Salsabila; Muhammad Fiqih Ubaidi; Saiful Bahri (Muhammadiyah International Public Health and Medicine Proceeding, 2022)
Mental health disorder is a psychological disease caused by a person's inability to deal with problems. The research method used in this study uses the type of literature review method. The research article search strategy is to use the Google Scholar search engine. The journals obtained from Google Scholar have gone through various ways of selecting the keywords, namely Islamic mental health, and have collected articles used for the literature review. There’s 4 literature for this article with the inclusion criteria used to search for literature review sources at this time are the research articles used within the last five years (2017-2022). From the perspective of Islam, health is more than just physical health; but also includes psychological or mental health.